Optimal surface preparation for wood anatomy research of invasive species by scanning electron microscopy : Optimalna priprema površine drva za istraživanje anatomije invazivnih vrsta drva pretražnim elektronskim mikroskopom - Merela, Maks (Array, 2020)
Research was done to develop the optimal method of wood surface preparation for scanning electron microscopy (SEM). Since 2018, environmental scanning electron microscope (ESEM™) FEI Quanta 250 has been installed at the Department of Wood Science and Technology in Ljubljana. We tested several methods for the pre-preparation and cutting of wood surfaces for SEM analyses. The samples had been either dried, soaked in water and frozen, impregnated with paraffin or simply moistened before cutting. We analysed wood surfaces obtained by splitting, sawing, planing, sanding and cutting on a sliding microtome with different blades. The effect of gold coating on the SEM image quality was also evaluated. Best results were obtained by cutting a pre-moistened surface on a sliding microtome with a low profile replaceable blade and gold coated afterwards. Determined methodology is technically less demanding, not time consuming and obtains results that satisfy needs for wood anatomy research at magnifications up to 12.000x. Guidelines for the optimal preparation of samples were prepared, and theoretical and practical basis for investigations of wood anatomy using SEM were provided. The method was afterwards used in analyses of invasive alien plant species – investigating their anatomical structure in the framework of the AlienPLAntSpEcies - APPLAUSE project (Urban Innovative Actions initiative). It was demonstrated that the use of the SEM opened new scope in detailed investigations of the wood structure and properties.